The Causal Model of Medical Students Love of Learning Need for Learning Passion for Searching and Global Innovation - Mahdi Mohammadi; Fahimeh Keshavarzi; Reza Naseri-Jahromi; Athar Rasekh-Jahromi (Kerman University of Medical Sciences, 2016)
Background & Objective: Students love of learning and need for learning lead to adopting of strategies which are the grounds for innovation especially at a global level Therefore the implementation of effective methods and strategies to create motivation and interest in learning in students seems essential The main purpose of this study was to study the relationship between medical students love of learning need for learning and passion for searching and global innovation Methods: This correlational descriptive study was carried out on students of Jahrom University of Medical Sciences Iran during the 20142015 academic years From among 338 students 200 students (86 men and 114 women) were selected through random sampling method and using the Cochran formula The data collection tools consisted of McFarlanes Love of Learning Questionnaire Mowen Lifelong Learning Questionnaire the Sensation Seeking Scale and Hurts Global Innovation Questionnaire Data were analyzed using the Pearson correlation coefficient and linear regression in SPSS software Results: The findings indicated that love of learning and need for learning were significant positive predictors of students global innovation (R2 = 044 P < 0001) and passion for searching (R2 = 027 P < 0001) The passion for searching was a direct positive and significant predictor of students global innovation (R2 = 037 P < 0001) The mediator variable of passion for searching had a key position in the relationship of love for learning and need for learning with students global innovation Conclusion: Based on the relationship between exogenous mediator and endogenous variables it seems that the love for learning is considered to be strength In addition through perseverance individuals will win various merits Thus universities should create the grounds for students innovation by providing the necessary conditions for the flourishing of talent and creating of interest and love of learning through the passion for searching